Non-operative treatment in advanced atraumatic osteonecrosis of the humeral head in patients under 50 years old: an observational study - Joon-Ryul Lim; Woo-Sung Do; Hsien-Hao Chang; Tae-Hwan Yoon; Yong-Min Chun (Scientific Reports)
Abstract The humeral head is the second most common anatomical site of osteonecrosis after the femoral head. Studies have reported satisfactory clinical outcomes after shoulder arthroplasty to treat osteonecrosis of the humeral head (ONHH). However, there are concerns regarding implant longevity in relatively young patients. This study investigated the effectiveness of non-operative treatment for atraumatic ONHH in relatively young patients. Thirty-two patients (41 shoulders, 9 bilateral) were included and received non-operative ONHH treatment consisting of pain management and self-stretching exercises. Treatment failure was defined as conversion to surgical treatment owing to difficulty performing activities of daily living with resting pain (Visual Analog Scale [VAS] ≥ 6) after 6 months of staged treatment. The mean follow-up was 73.6 months. The mean ONHH stage was 3.6 initially and 3.8 at final follow-up. Stage progression was observed in 14.6% (6/41) of the shoulders. No treatment failures occurred during follow-up. Between the initial visit and final follow-up, no significant differences in clinical outcomes, including resting pain, Single Assessment Numeric Evaluation score, forward flexion, and external rotation were observed; only internal rotation range of motion was observed to significantly decrease (p < 0.001). Non-operative treatment showed satisfactory results in relatively young patients with advanced atraumatic ONHH.